Brief considerations on the of ecological values (Revista do Tribunal Regional Federal da 3ª Região, 2015)
If we wanted to follow a line that would take us back to the earliest antecedents of the notion of law, in view of the discipline that now interests us - the Environment - we would arrive at a clearing where the seminal source/genesis of law would be present, however general or special it may be. This is because the authenticity of the origin of rights is the very existence of Man: Hominum causa omne ius constitutum est (D. 1, 5, 2, Hermog.). Based on this foundation, we arrive at a corresponding judgment that the dimension of values is engendered with the emergence of human life. Considering this sentence and in line with these axioms, the contemporary concern that reflects the dualism of man/environment comprises a social plastic that, prior to the idea of enjoyment, is undoubtedly connected to the essentiality of our living on the planetary geography. This imposes that the perspective of man/environment is connected to a broad platform of socio-ecological substrate. On the other hand, it is always appropriate to point out that, in the development of this theme, the impact of objective reality and the respective intersection in the basic needs of human life - in its original formulation - have demonstrated that all production of vital subsistence (subsidies to life) has been dependent on the ecological/environmental mattress. These focuses are also closely intertwined because the issue of productivity is intertwined with the requirements of the basic demands of the human being, as much as it is dependent on the countless constraints of eco/environmental resources. It is also possible to readily accept that the connection between the geoecological environment and the dogmas of legal science anathematize experiential and legal values, and that they are intertwined. It follows ipso facto that the dimensions of the disciplines of land law1 (in their public and private aspects) include all the norms of primary survival in both the social and individual sense. This list therefore includes developments in the branches of agrarian law, eco/environmental law and agro-industrial law, which are insinuated as univitelline legal subjects under the common sap of egalitarian formative and even potestative humus. But research into the exact points where they touch or repel each other, identify or exclude each other, always requires more careful and in-depth work, more complex and inductive, which few are willing to explore.
Keywords: environmental law; principles; background; safety; social function; sustainability